Bringing others into us: school leadership meeting the politics of identity - Billot, J (Common Ground Publishing Pty Ltd, 2007)
How does a school maintain a sustainable identity within the rapidly changing society in which it is positioned?As a result of global migrations of people, the demographics of societies are changing and creating increasingly diverse communities, resulting in a challenging context for school leadership. The ‘research territory’ (Morrison, Lumby & Sood, 2006, p.281) of diversity has mainly been occupied by those outside the domains of educational management and leadership, so this paper aims to redress that imbalance. By examining the connections between diversity of population and school identity, I identify how inclusive practices aimed at social equity can be used to draw diverse groups into a larger unifie school community. There has been much debate about what constitutes ‘diversity’ in general terms and, given the multiplicity of meanings for this concept, in this paper I focus on ethno cultural diversity which Au refers to as encompassing ‘groups with shared histories and cultural knowledge’ (1995,p.85). I refer to research finding of an international study to identify strategies and practices developed and implemented by principals in New Zealand to address increasing ethnocultural diversity. Identity can be viewed as the ‘combination of the internal experience of place and external participation in world and society’ (Cockburn,1983,p.1). The principal holds a pivotal role in facilitating school identity and as leadership emerges from social constructions of the self, so the principal works recursively with the concept of identity in the agency of leadership. I identify the tension between efforts to value diversity and the achievement of social cohesion through consensus building and contend that espoused concentration on issues arising from the multi dimensional nature of diversity can divert focus from the pursuit of equity.
Keywords: Ethnocultural diversity; Identity; School leadership